A TRANSLATION PRODUCT ANALYSIS OF CHATGPT BASED ON THE ERROR TAXONOMY BY VILAR ET AL. (2006): PROBLEMS AND SOLUTIONS - Hardiany, Dewi Rosnita; Pratama, Mochamad Rizqi Adhi (English Literature Department, Faculty of Economics, Law, and Humanities, 2025)
This study aims to analyze the translation product of ChatGPT by identifying the errors based on the error taxonomy proposed by Vilar et al. (2006). As AI-powered machine translation (MT) becomes increasingly prevalent, evaluating the quality of the output and identifying specific weaknesses is crucial. This research used a descriptive qualitative approach to examine 30 English-to-Indonesian translation outputs generated by ChatGPT. The analysis was guided by Vilar et al.'s error categories: missing words, word order, incorrect words, unknown words, and punctuation. Results show that while ChatGPT performs well in terms of fluency, some errors still occur in the form of incorrect words (33,3%), word orders (23,3%), missing words (20%), and punctuation (13,3%) and unknown words (10%). It can be concluded that the most frequent errors are incorrect words, word orders, and missing words. Proposed solution involves post-editing strategies by adapting translation techniques by Molina and Albir in order to make the translation result more accurate, natural, and aligned with the norms of the target language